2009
DOI: 10.1371/journal.pone.0006782
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Complement Pathway Deregulation Is Correlated with Dengue Severity

Abstract: BackgroundThe complement system, a key component that links the innate and adaptive immune responses, has three pathways: the classical, lectin, and alternative pathways. In the present study, we have analyzed the levels of various complement components in blood samples from dengue fever (DF) and dengue hemorrhagic fever (DHF) patients and found that the level of complement activation is associated with disease severity.Methods and ResultsPatients with DHF had lower levels of complement factor 3 (C3; p = 0.002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 48 publications
10
106
1
Order By: Relevance
“…However, the occurrence of thrombocytopenia, hemolysis, and acute kidney injury after resolution of the acute illness and presence of normal prothrombin time favors the diagnosis of HUS. Although pathogenesis of dengue involves activation of the classical complement pathway, alternative complement pathway dysregulation is also reported, as evidenced by transient depletion of CFH during the acute phase in patients with severe dengue relative to mild disease [18]. We speculate that unregulated [13] and E. coli O157:H7 [14] b post-transplant recurrence was attributed to endothelial microchimerism in this patient activation of alternative complement pathway due to CD46 deficiency might lead to severe dengue infection with circulatory compromise, acute kidney injury, and thrombotic microangiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of thrombocytopenia, hemolysis, and acute kidney injury after resolution of the acute illness and presence of normal prothrombin time favors the diagnosis of HUS. Although pathogenesis of dengue involves activation of the classical complement pathway, alternative complement pathway dysregulation is also reported, as evidenced by transient depletion of CFH during the acute phase in patients with severe dengue relative to mild disease [18]. We speculate that unregulated [13] and E. coli O157:H7 [14] b post-transplant recurrence was attributed to endothelial microchimerism in this patient activation of alternative complement pathway due to CD46 deficiency might lead to severe dengue infection with circulatory compromise, acute kidney injury, and thrombotic microangiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical studies demonstrated that DENV-infected patients, especially those with severe DF, show reduced levels of C3, C4 and factor B, together with increased catabolic rates of C3a and C1q [32], [33]. In addition, it has been reported that C3 degradation products and anaphylatoxins accumulate in the circulation of severely ill patients and peak on the day of maximum vascular leakage [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…DENV proteins inhibit complement activation (94). In addition, the levels of complement proteins, including C4, were altered in patients with severe DENV disease (95).…”
Section: Figmentioning
confidence: 99%